Intelligent electricity-saving road lamp controller - MINXIN LIANG (2000)
The utility model relates to a road lamp control device. The utility model comprises a brightness testing circuit, a controlling circuit, an output circuit, etc., wherein, the controlling circuit is composed of a single chip computer basic system, a display circuit, a clock circuit, a keyboard, etc. The brightness testing circuit and the keyboard are served as the inputting means of the single chip computer basic system, and the output of the single chip computer basic system is sent to the display circuit and the output circuit, and simultaneously is connected with the clock circuit. Two relays of the output circuit are respectively connected with two controlled road lamp circuits. Compared with the prior art, the utility model has the advantages of energy saving, convenient control, etc.